Effect of bovine ABCG2 polymorphism Y581S SNP on secretion into milk of enterolactone, riboflavin and uric acid. (29th October 2015) - Otero, J. A.; Miguel, V.; González-Lobato, L.; García-Villalba, R.; Espín, J. C.; Prieto, J. G.; Merino, G.; Álvarez, A. I.
Abstract : The ATP-binding cassette transporter G2/breast cancer resistance protein (ABCG2/BCRP) is an efflux protein involved in the bioavailability and milk secretion of endogenous and exogenous compounds, actively affecting milk composition. A limited number of physiological substrates have been identified. However, no studies have reported the specific effect of this polymorphism on the secretion into milk of compounds implicated in milk quality such as vitamins or endogenous compounds. The bovine ABCG2 Y581S polymorphism is described as a gain-of-function polymorphism that increases milk secretion and decreases plasma levels of its substrates. This work aims to study the impact of Y581S polymorphism on plasma disposition and milk secretion of compounds such as riboflavin (vitamin B2 ), enterolactone, a microbiota-derived metabolite from the dietary lignan secoisolariciresinol and uric acid. In vitro transport of these compounds was assessed in MDCK-II cells overexpressing the bovine ABCG2 (WT-bABCG2) and its Y581S variant (Y581S-bABCG2). Plasma and milk levels were obtained from Y/Y homozygous and Y/S heterozygous cows. The results show that riboflavin was more efficiently transported in vitro by the Y581S variant, although no differences were noted in vivo . Both uric acid and enterolactone were substrates in vitro of the bovine ABCG2 variants and were actively secreted into milk with a two-fold increase in the milk/plasma ratio for Y/S with respect to Y/Y cows. The in vitro ABCG2-mediated transport of the drug mitoxantrone, as a model substrate, was inhibited by enterolactone in both variants, suggesting the possible in vivo use of this enterolignan to reduce ABCG2-mediated milk drug transfer in cows. The Y581S variant was inhibited to a lesser extent probably due to its higher transport capacity. All these findings point to a significant role of the ABCG2 Y581S polymorphism in the milk disposition of enterolactone and the endogenous molecules riboflavin and uric acid, which could affect both milk quality and functionality.